Making it in public relations : an insider's guide to career opportunities - Mogel, Leonard (Lawrence Erlbaum Associates, 2002)
Mogel describes everything from the basics of vocational guidance, for those wanting to break into the public relations industry, to how different strategies have sparked the growth and enhancement of the industry in various corporate and industrial fields.